2019
DOI: 10.1016/j.physb.2018.11.029
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of in-plane strain on commensurate graphene/hexagonal boron nitride superlattices

Abstract: Due to atomically thin structure, graphene/hexagonal boron nitride (G/hBN) heterostructures are intensively sensitive to the external mechanical forces and deformations being applied to their lattice structure. In particular, strain can lead to the modification of the electronic properties of G/hBN. Furthermore, moiré structures driven by misalignment of graphene and hBN layers introduce new features to the electronic behavior of G/hBN. Utilizing ab initio calculation, we study the strain-induced modification … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…46 This study on the formation conditions of shear strain may give an insight for the use of strained h-BN in electronic devices, 2D heterostructures, and especially as a platform for tuning the electronic structure of graphene. 47 Discussion. In this study, growth was carried out at atmospheric pressure with 200:5 sccm of Ar/H 2 flow, potentially leading to the overgrowth at the exposed edges of APBs.…”
Section: Nano Lettersmentioning
confidence: 96%
See 1 more Smart Citation
“…46 This study on the formation conditions of shear strain may give an insight for the use of strained h-BN in electronic devices, 2D heterostructures, and especially as a platform for tuning the electronic structure of graphene. 47 Discussion. In this study, growth was carried out at atmospheric pressure with 200:5 sccm of Ar/H 2 flow, potentially leading to the overgrowth at the exposed edges of APBs.…”
Section: Nano Lettersmentioning
confidence: 96%
“…Strained h-BN was reported to have different characteristics to pristine h-BN, for example, causing phonon shift 46 . This study on the formation conditions of shear strain may give an insight for the use of strained h-BN in electronic devices, 2D heterostructures, and especially as a platform for tuning the electronic structure of graphene 47 .…”
Section: Shear Strain Band At Coalescence Boundary Of H-bn Spiral Clu...mentioning
confidence: 99%
“…In particular, great efforts have been devoted to the clarification of the band structure modulation around the Dirac cone induced by the hBN superlattice potential [13,[36][37][38][39][40][41][42][43][44][45][46]. It is reported that a band gap as large as around 40 meV emerges if graphene/hBN is nearly 0 • aligned, and the gap varies with respect to the twisting angle between the two layers [18,36,38,39,42,[45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%